Assessing the changes in marine microalgae diversity in the Nanji Islands Nature Reserve over the past decades using sediment eDNA - Li, Haotian; Xu, Alan Ningyuan; Yang, Zaibao; Lei, Yanli; Chen, Jiaxin; Zhan, Zifeng; Xu, Kuidong; Li, Tiegang; Xie, Shangwei (Frontiers in Marine Science, 2024)
The Nanji Islands, designated as one of China's national nature reserves, are renowned for their abundant microalgal resources. Changes in microalgae can serve as indicators of marine environmental shifts. Despite this significance, the absence of comprehensive historical records on microalgal diversity has limited the evaluation of marine environmental protection efforts. This study addresses this gap by analyzing surface sediments and sediment cores from the Nanji Islands, utilizing 210 Pb dating and employing environmental DNA (eDNA) technology to trace historical shifts in the molecular diversity of microalgae. Chloroplast gene fragments were amplified using rbcL primers, and 210 Pb dating determined the deepest sediment layer (78-80 cm) to date back to 1994. From the 70-72 cm layer to the 60-62 cm layer, the number of microalgal reads increased rapidly from 27,716 to 65,143, signifying enhanced abundance over the 10 years following the establishment of the nature reserve. This was followed by a deceleration in microalgal abundance growth over the subsequent 20 years, potentially reflecting variations in primary production of microalgae. Concurrently, the rise in operational taxonomic units (OTUs) and the Margalef index suggest a boost in microalgal diversity, which may be attributed to improvements in the marine environment. The microalgal community composition has shifted from a dominance of Dinoflagellata and Streptophyta to a predominance of Bacillariophyta, the change in phosphate would be one of the impact factors worth noting. This study provides foundational data on the historical changes in microalgae in the Nanji Islands and serves as a reference for exploring the relationship between environmental conditions and microalgal dynamics.